2003
DOI: 10.1074/jbc.m204937200
|View full text |Cite
|
Sign up to set email alerts
|

NAB2, a Corepressor of EGR-1, Inhibits Vascular Endothelial Growth Factor-mediated Gene Induction and Angiogenic Responses of Endothelial Cells

Abstract: In this study we have investigated the role of a specific corepressor of EGR-1, NAB2, to down-regulate vascular endothelial growth factor (VEGF)-induced gene expression in endothelial cells and to inhibit angiogenesis. Firstly, we show a reciprocal regulation of EGR-1 and NAB2 following VEGF treatment. During the initial phase EGR-1 is rapidly induced and NAB2 levels are down-regulated. This is followed by a reduction of EGR-1 and a concomitant increase of NAB2. Secondly, using the tissue factor gene as a read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 46 publications
2
90
0
1
Order By: Relevance
“…and NFAT) [27][28][29][30]. In cancer cells, the effects of oncogenic EGFR on TF are mediated through an NFκB dependent mechanism [10], as well as by processes involving AP-1 and c-Jun Nterminal kinase (JNK) activation [12].…”
Section: Discussionmentioning
confidence: 99%
“…and NFAT) [27][28][29][30]. In cancer cells, the effects of oncogenic EGFR on TF are mediated through an NFκB dependent mechanism [10], as well as by processes involving AP-1 and c-Jun Nterminal kinase (JNK) activation [12].…”
Section: Discussionmentioning
confidence: 99%
“…23 It has also been reported that EGR-1 and NAB-2 play pivotal roles in vascular biology, especially in VEGF-A-mediated angiogenesis. 53,54 However, obtaining evidence that EGR-1 directly regulates VEGF-A expression has heretofore been intractable because EGR-1 is immediately and transiently induced by various kinds of signals, and because conventional expression vector systems that result in sustained EGR-1 expression/overexpression reduce cell growth. 24,55 We therefore established EGR-1-inducible lung cancer cells to allow strict examination of the alterations caused by EGR-1 up-regulation, and we could successfully provide direct evidence that EGR-1 activates VEGF-A in lung cancer cells in a HIF-1␣-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…A VEGF-induced TF expression assay in HUVEC was used to demonstrate the direct binding of the aptamer to the HBD in vivo (16). HUVEC up-regulate the expression of TF in response to VEGF 165 , and this up-regulation can be suppressed by the aptamer (Fig.…”
Section: The Hbd Competes In Vivo With Full-length Vegf165 For Aptamermentioning
confidence: 99%